Impact of Tussigenic Stimuli on Perceived Upper Airway Sensation and Motor Cough Response Following Total Laryngectomy - Fullerton, Amy; Mou, Yuhan; Silver, Natalie; Chheda, Neil; Bolser, Donald C.; Wheeler-Hegland, Karen (Frontiers in Physiology, 2020)
Background Total laryngectomy (TL) is standard intervention for carcinoma of the head and neck or, in cases of non-functional larynx, as a result of disease or radiation exposure. Laryngeal extirpation serves as a unique human model of both recurrent and superior laryngeal nerve section and offers insight into motor and sensory aspects of cough: both volitional and in response to tussigenic stimuli. While motor changes in cough function are expected among those status post-TL due to postoperative reconstruction of the upper airway, motor cough parameters have not been well described and sensory aspects of cough are unknown in this population, which provides insight into a vagal denervation model in humans. Methods Data were collected from three groups totaling 80 adults (39 male), including 25 healthy younger adults (HYA), 27 healthy older adults (HOA), and 28 adults post-TL. Cough was elicited both upon command and in response to nebulized capsaicin. Outcome measures included urge to cough and cough airflows. Results Kruskal–Wallis test showed that two of the three groups differed significantly by urge to cough χ2(2, N = 244) = 8.974, p = 0.011. Post hoc analysis showed that post-TL subjects had reduced perceived urge to cough at all concentrations of capsaicin (p < 0.05). Cough airflows were significantly reduced for post-TL subjects compared to healthy controls in all metrics except post-peak phase integral (PPPI) for which HOA and TLs were comparable under both volitional and capsaicin-induced conditions. Conclusions These findings support the hypothesis that both cough airflow and sensations are significantly reduced in post-TL subjects when compared with HOA. Interestingly, HOA and post-TL subjects have comparably reduced UTC and cough airflows when compared to HYA. The only metric of cough airflow for which these groups differ is the PPPI, which may be a compensatory adaptation for reduced cough airflows and/or sensation.